2010
DOI: 10.1007/s10120-010-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of inflammatory cytokines in the progression of gastric cancer: friends or foes?

Abstract: Although the etiology of gastric cancer has been completely obscure for many decades, several considerable advances in the knowledge of the carcinogenesis and development of gastric cancer have been made in the present era. First, it is well known that Helicobacter pylori infection is associated with the carcinogenesis and development of gastric cancer, suggesting that chronic infl ammation may be implicated in the development of intestinal metaplasia and mutations in oncogenes that precede the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 74 publications
2
59
0
1
Order By: Relevance
“…Inflammation has been hypothesized to play a significant role in the etiology of gastric cancer [5]. Study shown circulating levels of inflammation-related cytokines such as IL-4, IL-6, IL-8, IL-10, and TNF-a were increased in patients with gastric cancer [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation has been hypothesized to play a significant role in the etiology of gastric cancer [5]. Study shown circulating levels of inflammation-related cytokines such as IL-4, IL-6, IL-8, IL-10, and TNF-a were increased in patients with gastric cancer [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ratio of Th1/Th2 decreases after surgery, resulting in a suppressed cell-mediated immunity [4]. Inflammatory cytokines suppress host anti-tumor immunity and lead to tumor growth and metastasis [5]. Surgical stresses also induce releases of catecholamines, which also stimulate tumor growth [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, surgery is the major known cure for the disease. Therefore, elucidation of the molecular mechanisms involved in gastric cancer and identification of valuable prognostic markers as well as novel therapeutic strategies is of essential clinical value (3).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is one of the most common malignant tumors and the second cause of cancer-related deaths worldwide (1,2). Chemotherapy for gastric cancer has been well developed, but a globally accepted standard chemotherapy and optical regimens have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%